THEORETICAL MODELS OF WELL-BEING: SUBJECTIVE, PSYCHOLOGICAL, SENSE OF LIFE, SELF-ESTEEM AND OPTIMISM - Gabriela Costa Ribeiro, Maria (Health and Society, 2021)
This work aimed to carry out a literature review on the theoretical models of well-being. Specifically, subjective well-being and psychological well-being, in addition to constructs that also promote quality of life, namely, the meaning of life, self-esteem and optimism. For this, the research was structured to present the definitions around the concept of well-being. Then, it tried to conceptualize, to know the psychological measures and studies that demonstrate the relation between sense of life, self-esteem and optimism. In this way, this review demonstrated how research conceives the phenomena in question, showing that it is not up to a single model to understand healthy psychological adjustment, but based on its multidimensionality observed in different constructs.